2017
DOI: 10.1016/j.aop.2017.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Statistical approach to tunneling time in attosecond experiments

Abstract: Tunneling, transport of particles through classically forbidden regions, is a pure quantum phenomenon. It governs numerous phenomena ranging from single-molecule electronics to donor-acceptor transition reactions. The main problem is the absence of a universal method to compute tunneling time. This problem has been attacked in various ways in the literature. Here, in the present work, we show that a statistical approach to the problem, motivated by the imaginary nature of time in the forbidden regions, lead to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 97 publications
(203 reference statements)
3
17
0
Order By: Relevance
“…In this respect, in our model, we quantify tunneling through the energy gap (potential barrier) and T-time using TEUR, which is equivalent to quantifying it through the transmission amplitude of the wave function. This follows in particular from the good agreement of our T-time with FPI [4,35] and SATT [74] for He-atoms. We see now why Ni et al [69] have found a high non-tunneled fraction as mentioned above (using a position criterion).…”
Section: Attoclock and Tunneling Time In Strong Field Interactionsupporting
confidence: 76%
See 1 more Smart Citation
“…In this respect, in our model, we quantify tunneling through the energy gap (potential barrier) and T-time using TEUR, which is equivalent to quantifying it through the transmission amplitude of the wave function. This follows in particular from the good agreement of our T-time with FPI [4,35] and SATT [74] for He-atoms. We see now why Ni et al [69] have found a high non-tunneled fraction as mentioned above (using a position criterion).…”
Section: Attoclock and Tunneling Time In Strong Field Interactionsupporting
confidence: 76%
“…Landsman et al have shown [4] a good agreement between the experimental result and the FPI. Demir et al [74] came to the same result of the T-time using a statistical approach to the T-time (SATT) based on FPI. Camus et al [75] claim that the agreement between theory and experiment in their work with Ar-, Kr-atom provides clear evidence for a nonzero T-time delay, however without clear details about their tunneling picture, i.e., adiabatic or nonadiabatic, which is certainly a crucial point.…”
Section: Attoclock and Tunneling Time In Strong Field Interactionmentioning
confidence: 93%
“…The advent of attophysics opens new perspectives in the study of time resolved phenomena in atomic and molecular physics [1][2][3][4], the tunneling process and the tunneling time (T-time) in atoms and molecules [5][6][7][8][9]. Attosecond science (asec=10 −18 s) concerns primarily electronic motion and energy transport on atomic scales and is of fundamental interest to the physics in general.…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, they (excepting FPI time with experiment-driven coarse-grained paths) fail to explain the experimental data, as was comparatively analysed and experimented in [15]. Nevertheless, two recent time definitions, the entropic tunneling time [52] and uncertainty-based tunneling time [54], are subliminal and agree well with He ionization data.…”
Section: Introductionmentioning
confidence: 86%
“…such that ψ is the wavefunction propagating in the direction, that is, ∇ψ ∝ p ψ (the momentum p along can be local or global, as was detailed in [52]). The equation (4), resulting from quantum generalization of d x/dt, is recognized to resemble the guiding equation in Bohmian mechanics [58].…”
Section: Quantum Travel Timementioning
confidence: 99%